ANALISIS SISTEM INFORMASI AKUNTANSI DALAM PROSEDUR PEMBELIAN UNTUK MENINGKATKAN PENGENDALIAN INTERNAL PADA PT MKDP - Irena, Florencia; Pikir, Toto Warsoko; Irawan, Ronny (Jurnal Akuntansi Kontemporer, 2014)
Internal control is a process designed to achieve the objectives of the company and the company's operations carried out in order to be effective and can guarantee of recording reliable financial statements. One of the company's operations are in the buying cycle is on the purchase of raw materials and the purchase of fixed assets. Company's accounting information systems required to support the compa-ny's procedures do become simple. PT MKDP is a manufacturing company specializing in the sale and purchase of wood and furniture. The company does not yet have the purchase information systems, resulting in improper purchase activity. The purpose of this study was to analyze the buying cycle accounting information system in PT MKDP to improve internal controls. The data analysis technique used in this study is a descriptive analysis that serves to explain the standard operating procedures by using analysis of accounting information systems.